Local disease–ecosystem–livelihood dynamics: reflections from comparative case studies in Africa - Leach, M.; Bett, Bernard K.; Said, M.; Bukachi, S.; Sang, R.; Anderson, N.; Machila, N.; Kuleszo, J.; Schaten, K.; Dzingirai, V.; Mangwanya, L.; Ntiamoa-Baidu, Y.; et al. (Royal Society, 2017)
This article explores the implications for human health of local interactions between disease, ecosystems and livelihoods. Five interdisciplinary case studies addressed zoonotic diseases in African settings: Rift Valley fever (RVF) in Kenya, human African trypanosomiasis in Zambia and Zimbabwe, Lassa fever in Sierra Leone and henipaviruses in Ghana. Each explored how ecological changes and human–ecosystem interactions affect pathogen dynamics and hence the likelihood of zoonotic spillover and transmission, and how socially differentiated peoples’ interactions with ecosystems and animals affect their exposure to disease. Cross-case analysis highlights how these dynamics vary by ecosystem type, across a range from humid forest to semi-arid savannah; the significance of interacting temporal and spatial scales; and the importance of mosaic and patch dynamics. Ecosystem interactions and services central to different people's livelihoods and well-being include pastoralism and agro-pastoralism, commercial and subsistence crop farming, hunting, collecting food, fuelwood and medicines, and cultural practices. There are synergies, but also tensions and trade-offs, between ecosystem changes that benefit livelihoods and affect disease. Understanding these can inform ‘One Health’ approaches towards managing ecosystems in ways that reduce disease risks and burdens. This article is part of the themed issue ‘One Health for a changing world: zoonoses, ecosystems and human well-being’.